2016
DOI: 10.1002/anie.201511301
|View full text |Cite
|
Sign up to set email alerts
|

Chemoproteomics‐Enabled Discovery of a Potent and Selective Inhibitor of the DNA Repair Protein MGMT

Abstract: We present a novel chemical scaffold for cysteine-reactive covalent inhibitors. Chloromethyl triazoles (CMTs) are readily accessed in only two chemical steps, thus enabling the rapid optimization of the pharmacological properties of these inhibitors. We demonstrate the tunability of the CMTs towards a specific biological target by synthesizing AA-CW236 as the first potent non-pseudosubstrate inhibitor of the O(6) -alkylguanine DNA methyltransferase (MGMT), a protein of major clinical significance for the treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 36 publications
0
37
0
1
Order By: Relevance
“…After each MGMT molecule transfers the methyl group from O 6 ‐meG, it will deactivate itself. Therefore, the cytotoxicity of TMZ is theoretically determined by the expression level of MGMT . Because of these factors, much effort has been directed towards increasing the TMZ chemosensitivity by downregulating the expression of MGMT of glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…After each MGMT molecule transfers the methyl group from O 6 ‐meG, it will deactivate itself. Therefore, the cytotoxicity of TMZ is theoretically determined by the expression level of MGMT . Because of these factors, much effort has been directed towards increasing the TMZ chemosensitivity by downregulating the expression of MGMT of glioma cells.…”
Section: Discussionmentioning
confidence: 99%
“…215 Wang has recently published the use of chloromethyl triazoles (CMTs) as a new warhead for covalent inhibitor. 226 A range of CMTs were synthesized using RuAAC and their activity against O 6 -alkylguanine DNA methyltransferase (MGMT) was determined, with 139 ( Fig. 24) being identified as a potent and selective covalent inhibitor of MGMT.…”
Section: Target-oriented Medicinal Chemistrymentioning
confidence: 99%
“…In another example, Wang et al showed that chloromethyltriazoles were a promising cysteine-reactive scaffold and that its reactivity could be tempered to confer selectivity for certain cysteines over others. The authors showcase a cloromethyltriazole AA-CW236 as the first potent, selective, non-pseudosubstrate inhibitor of the O(6)-alkyguanine DNA methyltransferase (MGMT) [46]. …”
Section: Abpp With Reactivity-based Probes or Reactive Chemical Smentioning
confidence: 99%